Insights from spectral stacking on the Hi content of cluster galaxies in various environments: a tale of two clusters - Healy, Julia Lynn (Department of Astronomy, 2022)
The environment in which a galaxy resides has long been known to have an impact on how the galaxy evolves. The denser the environment, the stronger the influence. Clusters of galaxies, which are some of the densest known cosmic environments, provide a unique opportunity to study the ongoing environmental processes influencing galaxy evolution. Optical studies have shown that galaxy clusters are typically home to a higher fraction of older elliptical, bulgedominated galaxies than the field which has a higher fraction of younger, disk-dominated galaxies. Which environmental processes are the cause of this morphology-density relation is still unknown. The dominant processes at play in the cluster environment tend to strongly impact the neutral hydrogen (H i) gas disks of galaxies. The H i disk often extends far out beyond the stellar disk making it susceptible to environmental processes before the stellar component of the galaxy is affected, and thus a useful tracer of the environment-driven galaxy evolution. In this thesis I study how the ongoing environmental processes in two galaxy clusters, the Coma cluster and Abell 2626, affect the average H i content of galaxies of different morphologies in different local environments or substructure. In the analysis of both clusters, I primarily use the H i stacking technique which uses the optical position and redshift information to extract global H i profiles of galaxies that are not necessarily directly detected in H i. The global profiles are aligned using the redshifts, and co-added to create an average H i spectrum with improved signal-to-noise statistics. Using yet-to-be published H i observations of the Coma cluster from the Westerbork Synthesis Radio Telescope, in combination with a new compilation of redshifts across the cluster, I explore the average H i content of galaxies located in different substructures within the cluster compared to cluster galaxies not associated with any substructure. While no conclusions can be made about which environment in Coma has a more dominant effect on the H i content, the analysis showed that there was a clear bimodality in the H i content of the cluster galaxies: either the galaxies were detected in H i, or the H i masses were well below the detection threshold. Where galaxies were not directly detected, they were found to be at least 10–50 times more H i deficient than field galaxies of the same type. Unlike the Coma cluster, Abell 2626 has not been as well studied, and so little is known about this cluster and its environs. In the second part of the thesis, I present new radio and optical observations of the cluster. Abell 2626 was observed by MeerKAT as part of the first open call for proposals. These observations have yielded H i data for Abell 2626 at the same H i mass sensitivity as the Westerbork observations of the Coma cluster, which is 2.5 times more nearby. Using the multi-object spectrograph, Hectospec, on the MMT telescope, we have created a spectroscopic catalogue of the Abell 2626 field that matches the MeerKAT observations and is 70% complete at r = 19.1 mag. The new spectroscopic catalogue around Abell 2626 enabled the characterisation of both the large scale structure in front of and behind the cluster, as well as the identification of substructure associated with the cluster. I am also able to determine that Abell 2626 is a rich cluster, comparable to the similarly sized Virgo cluster. I explore how the average H i content of galaxies of different luminosity, colour, and morphology change across the different local environments and substructure within the cluster. I find that late-type cluster galaxies located in substructures contain on average more H i than the late-type cluster galaxies not in substructures. I postulate that this suggests that the group environment protects the late-type galaxies from gas stripping mechanisms dominant in the global cluster environment. The H i stacking analysis shows that while Abell 2626 is not as H i deficient as the more massive Coma cluster, the Abell 2626 cluster galaxies do show a radial trend in the H i deficiencies as is observed in other clusters.